Bibliofilia e livros raros na perspectiva histórico-cultural: uma abordagem crítica às visões instituídas na Biblioteconomia e Ciência da Informação brasileira - Diná Marques Pereira Araújo (2017)
This research analyzes the relationship between Bibliophilia and the rare book in the modern era from the perspective of Cultural History, as a foundation for the dialogues with the History of the Book, the Collecting and the Bibliography. In theoretical-conceptual terms the History of the Book allowed us to observe the social contexts of the rare book through the Circuit of Communication proposed by Robert Darnton. On the other hand, Bibliophilia, presented as one of the manifestations of the Collection, subsidized the understanding of bibliophilic practices that led to the invention of rarity. In this sense, the connections between Bibliophilia and Bibliography are emphasized. Initially in terms of the concepts of Bibliography and then as to the detail of the historical-conceptual circumstances that promoted the production of specialized repertoires dedicated to Bibliophilia, which we identified as Bibliographies of Rare Books. Thus, having defined as main objective of the research to identify how the discourses on rarity from Bibliophilia are incorporated by the Brazilian Library and Information Science (B & CI) as guides for the elaboration of the concept of rare book, it was established complementary methodological aspects: one dedicated to the study of the Bibliographies of Rare Books from the 16th to the 20th centuries, pointing to historical foundations that built the rarity; and another one referring to the mapping of the concept of rare book in the production of Brazilian B & CI. As such, the data collection was carried out through bibliographic research and the results measured by establishing comparisons between the rare book concepts evidenced by B & CI with those forged by Bibliophilia. As a result, we point out the consequences of the adoption of criteria of rarity idealized by Bibliophilia to understand, in terms of the benefits and limitations, Brazilian bibliographic heritage in the present time.